Europe and fuel sulfur (The Oil & gas journal, 2001)
With its proposal to remove nearly all sulfur from gasoline and diesel fuel, the European Commission threatens to follow the precautionary principle on global warming up an economic smokestack. The EC's proposal would certainly raise the already high prices of vehicle fuel in Europe. The promised gains are subject to great doubt. And the overarching goal - carbon dioxide reductions as a precaution against global warming - teeters on a weakening hypothesis. This is a whimsical governance. European oil companies owe it to their customers to say so.